Impact of Light and Temperature on Growth, Intracellular and Extracellular Pigment, and Lovastatin Yield by Monascus ruber in Synthetic Medium - K. Suganya; A. Usha Raja Nanthini; Jayaraman Narenkumar; Subramani Abilaji; Aruliah Rajasekar; Subpiramaniyam Sivakumar; S. Prasath; Hesham S. Almoallim; Tahani Awad Alahmadi (Advances in Materials Science and Engineering)
The development of alternate sources for the production of natural pigments has been targeted to overcome the utilization of artificial coloring, which is dangerous to human health and the environment. Dyes extracted from microbial sources are more important for beneficial food industry use, especially Monascus spp. produces several critical secondary metabolites such as lovastatin, g-amino butyric acids, monascodilone, monascorubramine, monascin, ankaflavin, rubropunctatin, and citrinin. Lovastatin is a fungal polyketide that inhibits the rate-limiting enzymes HMG-CoA reductase, an essential precursor in cholesterol biosynthesis. The light source regulates fungi’ growth, metabolism, and reproduction and is necessary for fungi’ existence and distribution. The impact of different color lights (red, green, blue, yellow, and white, darkness) and different temperatures (27°C and 37°C) on extracellular and intracellular pigment yield, lovastatin production, and biomass of Monascus ruber was studied, and appropriate incubation temperature and time enhance the intracellular, extracellular pigment, and biomass production. However, when exposed to other color lights, fungus growth and pigment yield are significantly reduced in Monascus ruber. Then, fungi and pigment yield development is decreased when exposed to other color lights. It can be concluded that darkness influenced pigment production and biomass yield at both temperatures (27°C and 37°C). Similarly, the production of lovastatin and its concentration were analyzed by HPLC. The highest concentration of lovastatin was obtained at 27°C when exposed to red color light (302.6 mg/ml for extracellular fermentation broth) and (86.7 mg/ml for intracellular fermentation broth). At 37°C, the highest concentration of lovastatin was obtained from (571.5 mg/ml extracellular fermentation broth) when exposed to darkness and (170.4 mg/ml intracellular fermentation broth) exposed to red color light. Thus, the result provides the knowledge to enable us to explore the pigments and lovastatin yield for functional foods and large-scale industrial applications.